Respuesta :

Answer:

-1

Step-by-step explanation:

Substitute the given values into the expression and solve:

(g + h)^3 = (2 - 3) ^3 = (-1)^3 = -1

hope this helps! <3

Answer: [tex]\Large\boxed{-1}[/tex]

Step-by-step explanation:

Given expression

(g + h)³

Given information

g = 2

h = -3

Substitute values into the given expression

= [(2) + (-3)]³

Simplify values in the parenthesis

= (2 - 3)³

= (-1)³

Simplify the exponents

[tex]\Large\boxed{-1}[/tex]

Hope this helps!! :)

Please let me know if you have any questions